ACTIVE AND PASSIVE VOICE USAGE IN ACADEMIC WRITING (Yangi O'zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2026)
One essential stylistic decision in academic writing is the usage of active and passive voice. The purposes, benefits, and drawbacks of both voices in academic fields are examined in this article. The study shows that a strategic and context-dependent balance between active and passive constructions is necessary for effective academic writing by examining academic texts and linguistic research.